1996
DOI: 10.1002/j.1460-2075.1996.tb00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid-independent assembly of coronavirus-like particles by co-expression of viral envelope protein genes.

Abstract: Budding of enveloped viruses has been shown to be driven by interactions between a nucleocapsid and a proteolipid membrane. By contrast, we here describe the assembly of viral envelopes independent of a nucleocapsid. Membrane particles containing coronaviral envelope proteins were assembled in and released from animal cells co‐expressing these proteins' genes from transfected plasmids. Of the three viral membrane proteins only two were required for particle formation, the membrane glycoprotein (M) and the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
582
1
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(619 citation statements)
references
References 61 publications
32
582
1
4
Order By: Relevance
“…These smooth surfaced particles are probably an intermediate particle in virus assembly. The formation of VLPs by these two proteins has been reported for other coronaviruses [16][17][18][19], and a very recent report has been published regarding the production of SARS-VLPs by multiple co-infection with single baculoviruses expressing M, E and S proteins individually. In this report, the VLPs did not bud from the insect infected cells but instead they were isolated from cell lysates [24].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These smooth surfaced particles are probably an intermediate particle in virus assembly. The formation of VLPs by these two proteins has been reported for other coronaviruses [16][17][18][19], and a very recent report has been published regarding the production of SARS-VLPs by multiple co-infection with single baculoviruses expressing M, E and S proteins individually. In this report, the VLPs did not bud from the insect infected cells but instead they were isolated from cell lysates [24].…”
Section: Discussionmentioning
confidence: 85%
“…Thus, we can hypothesize that as with other coronaviruses [18,33,34], the protein component of these particles essentially consists of a matrix of laterally interacting M proteins, which in some way require the E protein for budding and, if available, the S protein is incorporated by specific interactions with M. We showed that the VLPs that were formed consisted of only the M, E and S proteins but not the N protein, indicating that N protein was not able to be incorporated. However, it was not unexpected that the SARS-CoV like particles were formed without the inclusion of nucleocapsid protein, as other coronaviruses also form VLPs in the absence of the N protein [16].…”
Section: Discussionmentioning
confidence: 94%
“…Expression of E and M alone is sufficient for virus-like particle (VLP) assembly. [1][2][3] E protein containing vesicles are released from cells when E is expressed alone. 4 E protein may also be involved in determining the virus budding site at the endoplasmic reticulum-Golgi intermediate compartment membrane (ERGIC).…”
Section: Introductionmentioning
confidence: 99%
“…The four structural proteins, the spike (S) glycoprotein, the envelope (E) glycoprotein, the membrane (M) glycoprotein and the nucleocapsid (N) protein, are encoded by subgenomic mRNAs (sgRNAs) 2, 3, 4 and 6, respectively (Stern & Sefton, 1982;Lai & Cavanagh, 1997 non-structural proteins, 3a, 3b, 5a and 5b, are also encoded by sgRNAs 3 and 5. One of the distinguishing features of group 3 coronaviruses is that the third open reading frame (ORF) (3c) of the tricistronic mRNA 3 encodes the E protein, which, together with the M protein, plays an essential role in virus-particle assembly (Bos et al, 1996;Vennema et al, 1996).With the exception of isolates from chicken, turkey and pheasant, only a small amount of experimental work has been carried out to study the host range of avian coronaviruses. On the basis of antigenicity and partial sequence data from isolated viruses, there are at least two additional avian species (pigeons and guineafowl) that are susceptible to IBV-like coronaviruses (Barr et al, 1988;Ito et al, 1991).…”
mentioning
confidence: 99%